Central Lesions With Selective Semicircular Canal Involvement Mimicking Bilateral Vestibulopathy - Chen, Luke; Halmagyi, G. Michael (Frontiers in Neurology, 2018)
Bilateral vestibulopathy (BVP), which is due to peripheral lesion, may selectively involve certain semicircular canals (SCC). Recent eye movement recordings with search coil and video head impulse test (HIT) have provided insight in central lesions that can cause bilateral and selective SCC deficit mimicking BVP. Since neurological signs or ocular motor deficits maybe subtle or absent, it is critical to recognize central lesions correctly since there is prognostic and treatment implication. Acute floccular lesion causes bilateral horizontal SCC (HC) impairment whilst leaving vertical SCC function unaffected. Vestibular nuclear lesions affect bilateral HC and posterior SCC (PC) function, but anterior SCC (AC) function is spared. When both eyes are recorded, medial longitudinal fasciculus lesions cause horizontal dysconjugacy in HC function and catch-up saccades, as well as selective deficiency of PC over AC function. Combined peripheral and central lesions may be difficult to distinguish from BVP. Anterior inferior cerebellar artery stroke causes two types of deficits: 1. ipsilateral pan-SCC deficits and contralateral HC deficit, and 2. bilateral HC deficit with vertical SCC sparing. Metabolic disorders such as Wernicke encephalopathy characteristically involve HC but not AC or PC function. Gaucher disease causes uniform loss of all SCC function but with minimal horizontal catch-up saccades. Genetic cerebellar ataxias and cerebellar-ataxia neuropathy vestibular areflexia syndrome typically do not spare AC function. Whilst video HIT does not replace the gold-standard, search coil HIT, clinicians is now able to rapidly and accurately identify specific pattern of SCC deficits which can aid differentiation of central lesions from BVP.